The Importance of Strategic Planning With Modern Trends in Education - Berlian Nursyanti Mahardhika; Setya Raharja (STAI Hubbulwathan Duri, 2023)
This study analyzes strategic planning in the educational environment that can contribute to changes in the quality of education tailored to the needs and progress of the times and current trends. The main objective of this research is to study strategic management and strategic planning in the educational environment to improve the quality of education in modern trends. This research is literature research or data collection exploring the research object through several library information studies. Strategic planning is a vital method for educational institutions to succeed and thrive. This can become more significant at the start or extension of learning in a program. With strategic planning, an educational institution, taking into account relevant internal and external environmental factors, can be better prepared to assess and set long-term directions and develop and implement strategies to achieve long-term goals. The process includes a series of organizational activities that begin with the concept of organizational goals and strategic goals.